Evaluation of HBsAg, anti-HCV, anti-HIV and VDRL test results in blood donors - Canan Ağalar (Journal of Clinical and Experimental Investigations, 2011)
Objectives: The most frequently encountered complication in the transfusion of blood and blood products are transmitted infections from these products. Infections caused by hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) remain the leading most important health problems in the transfusion of blood and blood products worldwide. Therefore, screening tests such as HBsAg, anti-HCV, anti-HIV, and RPR or VDRL for Treponema pallidum are mandatory tests to look at before transfusion of blood and blood products. In this study, the screening tests results of blood donors examined were evaluated and the results were compared with the results of the other blood banks stated in our country.Materials and methods: Screening tests results of a total of 784 blood donors, which have been admitted the Kırıkkale University Hospital Blood Center for blood donation between January 2003 and December 2004, evaluated retrospectively. Blood samples which taken from blood donors before blood donation were investigated for HBsAg, anti-HCV, and anti-HIV tests with chemiluminescense (ELISA) method by automated analyzer. VDRL screening test was investigated by commercial test kit.Results: A total of 734 (93.7%) of 784 blood donors were male and 50 (6.3%) were female. HBsAg was positive in 11 (1.4%) blood donors and anti-HCV in 2 (0.2%) blood donors. None of the blood donors were found to anti-HIV and VDRL seropositivity.Conclusions: Seropositivity rates of HBsAg and anti-HCV were lower than that of Turkey in general. J Clin Exp Invest 2011; 2 (4): 416-419